Ventricular activation and repolarization in response to physiological and conventional pacing using ultra-high-frequency electrocardiography - Saúl Palacios; Radovan Smisek; Karol Curila; Uyen Nguyen; Frits W. Prinzen; Josef Halamek; Filip Plesinger; Pavel Jurak; Javier Ramos; Juan Pablo Martínez; Esther Pueyo (PLoS ONE, 2026)
Background Physiological pacing targeting the cardiac conduction system is increasingly being adopted as an alternative to conventional right ventricular (RV) pacing for the treatment of bradyarrhythmias, although its effects on ventricular repolarization remain underexplored. Objective This study evaluates depolarization and repolarization responses to different pacing techniques using ultra-high-frequency electrocardiograms (UHF-ECGs). Methods Temporary pacing was performed at different cardiac areas in 178 patients with bradycardia. Depolarization was assessed via QRS duration (QRS d ), QRS area (QRS a ), ventricular dyssynchrony (e-DYS), and activation time dispersion (dAT computed from leads V1-V6 and dAT 4-6 from leads V1-V6). Repolarization was analyzed using the corrected QT interval (QTc), T-wave area (T a ), Periodic Repolarization Dynamics (PRD), and repolarization time dispersion (dRTc and dRTc 4-6 ). Results His bundle pacing (HBP) preserved ventricular activation patterns similar to spontaneous rhythm. Left bundle branch pacing (LBBP) induced moderate depolarization changes, primarily due to delayed right ventricular activation, while maintaining left ventricular synchrony. In particular, dAT showed no significant differences between HBP and spontaneous rhythm, while differences between LBBAP and spontaneous rhythm were significant but below 7 ms in median. When restricted to the left ventricle (LV), no significant differences in dAT 4-6 were found between LBBAP and spontaneous rhythm. Importantly, e-DYS for HBP showed similar values to spontaneous rhythm, LBBP led to a significant reduction (median differences approximately 20 ms), and RVP was associated with a significant increase (above 15 ms in median). In line with these results, QRS d and QRS a showed the largest values for RVP. In terms of ventricular repolarization, median differences in the QTc interval between pacing modes and spontaneous rhythm were below 3 ms for HBP, above 1 ms for LBBP, and above 20 ms for RVP. All pacing modes led to a reduction in PRD, with the most marked reductions observed for LBBP, particularly for selective LBBP, with median changes with respect to spontaneous rhythm of 4.6 degrees. RT and RTc showed similar trends for all pacing techniques. T a , however, showed median differences with respect to spontaneous rhythm above 100 and 34 μ Vs when pacing the RV at the apex and the septum, respectively, whereas such median differences were below 16 μ Vs for HBP and below 2 μ Vs for LBBP. Conclusion Physiological stimulation via HBP or LBBAP generates ventricular depolarization and repolarization responses that more closely resembles that of spontaneous rhythm, in high contrast to the largely different response induced by RV pacing. HBP and LBBAP have distinct technical characteristics, including differences in capture thresholds, lead stability, and procedural aspects. These techniques serve as alternatives to conventional RV pacing.